Analysis of Organizational Behavior in Improving Quality Based on Pesantren - Hikmatul Hidayah (Yayasan Avicenna, 2022)
This study aims to analyze organizational behavior as a strategic factor in improving institutional quality at Ma'had Aly Nurul Jadid, located in Paiton, Probolinggo. The research employs a descriptive qualitative approach, focusing on in-depth understanding of phenomena that emerge and develop within the organization. The researcher seeks to explore how patterns of behavior among institutional actors influence the performance and progress of the institution. Data collection was conducted through direct observation, allowing the researcher to engage naturally with the setting and capture contextual nuances. The primary instrument used in this study is the researcher himself, supported by assistants when necessary. In line with the principles of qualitative inquiry, data were gathered through processes of questioning, listening, observing, and taking notes to ensure the authenticity of the findings. The data analysis was carried out in three stages: data presentation, data reduction, and conclusion drawing, with a focus on identifying recurring patterns and meaningful themes. The findings indicate that the organizational behavior at Ma'had Aly Nurul Jadid is reflected through several key characteristics, including attention to detail, institutional stability, team orientation, individual consideration, focus on results, and a proactive or aggressive attitude toward achieving institutional goals. These behavioral traits contribute significantly to building a strong organizational culture that supports continuous institutional development.